2018
DOI: 10.14740/gr912w
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Adolescent Cronkhite-Canada Syndrome

Abstract: The Cronkhite-Canada syndrome (CCS) was first reported in 1955, since then more than 500 cases have been reported, indicating an estimated incidence of one case per 1 million inhabitants. The syndrome occurs predominantly in male, with a ratio of three males to two females. Because of the rarity of the syndrome, there are no evidence-based therapies and the treatments described include a combination of therapies, but none is consistently effective. Surgery is usually reserved for the treatment of complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The previous study with large sample size has reported that males and people aged 50–60 were the high-risk group [5‒7]. There were also a few sporadic cases reported among young people [9, 10]. Our findings from Chinese CCS patients were very similar with those results from other areas.…”
Section: Discussionsupporting
confidence: 88%
“…The previous study with large sample size has reported that males and people aged 50–60 were the high-risk group [5‒7]. There were also a few sporadic cases reported among young people [9, 10]. Our findings from Chinese CCS patients were very similar with those results from other areas.…”
Section: Discussionsupporting
confidence: 88%
“…[ 21 ] In this case, the patient’s clinical symptoms improved after 3 months of application of trace elements. CCS is characterized by the presence of diffuse gastrointestinal polyps, and multiple diffuse gastrointestinal polyps often involve the entire gastrointestinal tract outside the esophagus, [ 22 ] It is most commonly found in the stomach and colon, followed by the small intestine and rectum. Most of the gastric polyps and colonic polyps are sessile, mucosal congestion, and rare punctate bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with juvenile polyposis syndrome, CCS polyps have fewer pedicles, inflammatory cell infiltration and edema in the lamina propria, and polyps have mucous abnormalities. [ 22 ] In addition, juvenile polyposis syndrome does not have epidermal features is also a differential point. [ 26 ] Despite the high rate of coincidence between CCS with gastrointestinal and colorectal cancers, it is unclear whether CCS is precancerous or whether it is associated with progression of conventional adenoma-carcinoma sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-losing enteropathy is often observed in CCS because of polypoid lesions in the GI tracts. The mean age of initial diagnosis of CCS is between 50 and 60 years [3] and young patients have rarely been reported [4, 5].…”
Section: Discussion/conclusionmentioning
confidence: 99%